Carbon and glass fibre-reinforced hybrid composites in flexure - Dong, Jonathan (2025)
This study investigates the flexural behaviour of carbon and glass fibre-reinforced hybrid composites using a finite element analysis (FEA)-based approach. Hybrid composites combine the strengths of different fibre types to enhance material performance, with carbon and glass fibres being selected for their distinct mechanical properties. The primary objective is to evaluate the flexural strength and failure mechanisms of these composites, focusing on the effects of hybrid layups and the interlaminar stresses that can lead to delamination. Nine different layups of hybrid composites, varying in the number of glass/epoxy plies, were analysed under three-point bending conditions. The study considers two predominant failure modes: microbuckling and delamination. Results show that delamination is the most likely failure mode, particularly at higher interlaminar shear stresses, while microbuckling is less critical in comparison. The predicted flexural strengths, based on delamination criteria, align closely with experimental data, with relative differences less than 2 %, demonstrating the significant influence of stacking sequence on hybrid composite performance. The findings highlight the complex interplay of fibre types and stacking sequences, providing valuable insights into the design and optimization of carbon and glass fibre-reinforced hybrid composites for engineering applications.